Enabling Efficient Late‐Stage Functionalization of Drug‐Like Molecules with LC‐MS and Reaction‐Driven Data Processing. Issue 47 (20th December 2017) - Yao, Huifang; Liu, Yong; Tyagarajan, Sriram; Streckfuss, Eric; Reibarkh, Mikhail; Chen, Kuanchang; Zamora, Ismael; Fontaine, Fabien; Goracci, Laura; Helmy, Roy; Bateman, Kevin P.; Krska, Shane W.
Abstract : Late‐stage functionalization (LSF) through C–H functionalization of drug leads is a powerful synthetic strategy for drug discovery. A key challenge in LSF is that multiple regioisomeric products are often generated, which requires slow and laborious product isolation and structure confirmation steps. To address this, an analytical approach using LC‐HR‐MS/MS coupled with automated chemically aware data processing was developed. Using this method to analyse reaction screening arrays based on three common C–H functionalization chemistries with a set of marketed drugs, the relative amount and localization of chemical modification could be determined for each regioisomeric product generated in the screening. This approach allows one to construct a workflow in which the various regioisomeric products of a given transformation are triaged according to their site of modification, allowing downstream isolation and structure elucidation efforts to focus on those analogues of highest interest, leading to an overall increase in productivity of the LSF strategy. Abstract : Better late (and fast!) than never: Complex product mixtures resulting from late‐stage functionalization chemistries applied to drug‐like molecules are quickly triaged using LC‐MS and "chemistry‐aware" data processing tools.